2012
DOI: 10.1063/1.4714606
|View full text |Cite
|
Sign up to set email alerts
|

Tendency of spherically imploding plasma liners formed by merging plasma jets to evolve toward spherical symmetry

Abstract: Three dimensional hydrodynamic simulations have been performed using smoothed particle hydrodynamics (SPH) in order to study the effects of discrete jets on the processes of plasma liner formation, implosion on vacuum, and expansion. The pressure history of the inner portion of the liner was qualitatively and quantitatively similar from peak compression through the complete stagnation of the liner among simulation results from two one dimensional radiationhydrodynamic codes, 3D SPH with a uniform liner, and 3D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 34 publications
(45 reference statements)
0
25
0
1
Order By: Relevance
“…For the most conservativeZ = 1.4 of the 30%/70% mixture case, n merged = 5.0-5.3×10 14 cm −3 , and n merged /n single = 2.1-2. 4. These values are summarized in Table I.…”
Section: Observation Of Merged-jet Densities Exceeding That Of Inmentioning
confidence: 99%
See 3 more Smart Citations
“…For the most conservativeZ = 1.4 of the 30%/70% mixture case, n merged = 5.0-5.3×10 14 cm −3 , and n merged /n single = 2.1-2. 4. These values are summarized in Table I.…”
Section: Observation Of Merged-jet Densities Exceeding That Of Inmentioning
confidence: 99%
“…One study concluded that a series of shocks occurring during plasma liner convergence would degrade the implosion performance, 50 while the other showed that initial non-uniformities arising from jet merging were largely smeared out by the time of peak compression. 4 More detailed studies are needed to resolve the discrepancy. We envision a five-jet experiment on PLX followed by a 30-or 60-jet experiment to study this and other issues.…”
Section: On the Use Of Merging Plasma Jets For Forming Sphericallmentioning
confidence: 99%
See 2 more Smart Citations
“…The efficiency of plasma guns creating and launching the jets can be optimized for a given velocity. Several recent studies have investigated various aspect of PJMIF: [11][12][13][14][15][16][17][18][19][20][21]. Methodical experimental efforts were initiated at Los Alamos National Lab (LANL) [22,-24] in collaboration with Hyper V Technologies [10,25], and the University of New Mexico [26].…”
mentioning
confidence: 99%